2022
DOI: 10.1039/d1ta10940e
|View full text |Cite
|
Sign up to set email alerts
|

A unique 2.1 V “Water in Salt” elemental sulfur based Na-ion hybrid storage capacitor

Abstract: The aqueous sodium-ion hybrid capacitor is a novel energy storage device, reconciles high energy and power density in a single device along with the inherent safety and conductivity of an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…When applied this WIS electrolyte in S@MNC-600//Na 0.44 MnO 2 hybrid capacitor, a working potential of 2.1 V with an impressive energy density and power density could be achieved. [198] Likewise, the WIS electrolytes are conductive to reversible plating/stripping of the Zn anode. Zhang et al proposed a low-cost WIS electrolyte of 30 m ZnCl 2 for a reversible Zn metal anode.…”
Section: Aqueous Electrolytesmentioning
confidence: 99%
“…When applied this WIS electrolyte in S@MNC-600//Na 0.44 MnO 2 hybrid capacitor, a working potential of 2.1 V with an impressive energy density and power density could be achieved. [198] Likewise, the WIS electrolytes are conductive to reversible plating/stripping of the Zn anode. Zhang et al proposed a low-cost WIS electrolyte of 30 m ZnCl 2 for a reversible Zn metal anode.…”
Section: Aqueous Electrolytesmentioning
confidence: 99%
“…219,220 Considering the above needs, Kumar et al rst demonstrated a Na-ion/ S hybrid capacitor using mesoporous nitrogen-containing carbon (MNC) anchored sulfur as the anode, Na 0.44 MnO 2 as the anode material, and 17 M NaClO 4 as the electrolyte. 221 A battery-type material, i.e., singlet sulfur, was introduced into the capacitance-type tubular MNC electrode to increase its capacity and balance the reaction kinetics. The WIS electrolyte (17 M NaClO 4 ) not only expanded its operating window to nearly 2.75 V, but also exhibited signicantly low solvent activity.…”
Section: Aqueousmentioning
confidence: 99%
“…[9][10][11][12] Carbon materials usually have a high specific surface area, good conductivity and chemical stability, abundant reserve, and are easy to produce and process, and non-toxic. [13][14][15][16] There are currently many issues associated with the combustion of fossil fuels and waste generation, and sustainable industrial growth is much focused on. 17 Biomass is a readily available, inexpensive, easy to modify, environmentally friendly, and renewable resource.…”
Section: Introductionmentioning
confidence: 99%